Gain-Scheduled Control of Linear Differential Inclusions Subject to Actuator Saturation - Li, Pengyuan; Wu, Yuhu; Sun, Xi-Ming; Lang, Zi-Qiang (IEEE transactions on industrial electronics (1982), 2019)
This paper focuses on the problem of robust stabilization of linear differential inclusions subject to actuator saturation. A continuous set of nonlinear controllers is constructed by a parameter-dependent convex hull Lyapunov function to avoid actuator saturation for known worst-case disturbances. The controller, which can achieve the best closed-loop performance while complies the saturation bound, is selected at each time, based on the closed-loop states. Thanks to the application of the continuous dynamic gain-scheduled control law, the internal stability and guaranteed disturbance attenuation can be obtained simultaneously. A quarter-car active suspension system is studied to demonstrate the benefit of the proposed method.